2015
DOI: 10.1017/s1351324915000406
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual native language identification

Abstract: We present the first comprehensive study of Native Language Identification (NLI) applied to text written in languages other than English, using data from six languages. NLI is the task of predicting an author's first language using only their writings in a second language, with applications in Second Language Acquisition and forensic linguistics. Most research to date has focused on English but there is a need to apply NLI to other languages, not only to gauge its applicability but also to aid in teaching rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 81 publications
2
42
0
Order By: Relevance
“…During the system development, we also experimented with the advanced architectures of neural networks, such as convolutional networks, recurrent networks, ResNets, DenseNets and pretrained word embeddings but none of them performed better than the linear SVM baseline. Malmasi et al (2015b) previously showed that even NLI systems working with just written essays can outperform human decisions. Our experiments revealed that adding information extracted from the spoken responses of non-native English speakers results into a substantial improvement in Table 5: Performance of five stand-alone classifiers used in the homogeneous FUSION system measured on the development test set.…”
Section: Resultsmentioning
confidence: 99%
“…During the system development, we also experimented with the advanced architectures of neural networks, such as convolutional networks, recurrent networks, ResNets, DenseNets and pretrained word embeddings but none of them performed better than the linear SVM baseline. Malmasi et al (2015b) previously showed that even NLI systems working with just written essays can outperform human decisions. Our experiments revealed that adding information extracted from the spoken responses of non-native English speakers results into a substantial improvement in Table 5: Performance of five stand-alone classifiers used in the homogeneous FUSION system measured on the development test set.…”
Section: Resultsmentioning
confidence: 99%
“…Analyzing the language produced by learners could provide insight into the limitations of learners' vocabulary. Learner corpora, widely used in the task of Native Language Identification (Malmasi and Dras, 2014;Malmasi and Dras, 2015b) could be useful here.…”
Section: Resultsmentioning
confidence: 99%
“…While most of the NLI research has been on English, there is a significant amount of work on other language texts such as Chinese, Finnish and Arabic (Malmasi and Dras, 2015;Malmasi, 2016). Starting form surface linguistic forms such as words and characters to deeper syntactic structures, a range of features have been explored for this task in the past five years.…”
Section: Introductionmentioning
confidence: 99%